ANALISIS IMPLEMENTASI PRINSIP-PRINSIP GOOD GOVERNANCE DALAM PENERBITAN BUKU PEMILIK KENDARAAN BERMOTOR DUPLIKAT OLEH POLRI DI SISTEM ADMINISTRASI MANUNGGAL SATU ATAP KOTA MEDAN - Reskyani widya sulastini, Muhammad Huzbullah (NERACA KEADILAN, 2025)
The application of good governance principles in public services is a crucial element in creating a transparent, accountable, effective, and participatory government system. One of the public services that is closely related to this is the issuance of duplicate Motor Vehicle Ownership Certificates (BPKB) by the Indonesian National Police through the Medan City One-Stop Integrated Administration System (Samsat). The background of this study is based on various problems in practice in the field, such as low information transparency, limited complaint systems, and the emergence of illegal levies that indicate the suboptimal implementation of good governance principles. This study aims to analyze how the implementation of good governance principles - which include transparency, accountability, effectiveness, efficiency, community participation, and the rule of law - in the process of issuing duplicate BPKBs at the Medan City Samsat. In addition, this study also identifies the obstacles faced and formulates recommendations for improving services based on good governance. The results of the study indicate that the implementation of good governance principles is still suboptimal. Information transparency is not evenly distributed, the complaint system has not been running effectively, digitalization of services is still limited, and community participation is not formally facilitated. The supremacy of law has also not been fully enforced, as indicated by the continued discovery of illegal levies. Therefore, suggested improvements include strengthening digitalization of services, training officers, developing monitoring and evaluation systems, and increasing socialization to the community. This study is expected to be a reference in improving the quality of professional and integrity-based public services.